Potentially useful flora from the tropical rainforest in central Veracruz, Mexico: considerations for their conservation - Burgos-Hernández, Mireya; Castillo-Campos, Gonzalo; Vergara Tenorio, María del Carmen (Instituto de Ecología, A.C., 2014)
Tropical rainforests have been a valuable source of resources for human kind. However, this ecosystem is disappearing at an alarming rate, with only isolated fragments remaining in inaccessible zones and showing high probability of disappearing. The aim of this study was to identify tropical rainforest plant species with potential for human use in the central region of Veracruz, Mexico. A floristic inventory was compiled of rainforest fragments and secondary vegetation using the plotting method. The total area sampled was 5600 m2. Using the equation Clench model, the proportion of species inventoried was assessed. This was 85% (tq = 0.85) for the rainforest and 90% (tq = 0.9) for the secondary vegetation. A total of 338 species, 210 genera and 89 families were recorded. Using semi-structured interviews with locals, a list of useful plants was drawn up and it was found that people recognized and used 47% of the species inventoried. Additionally, contingency tables and the Spearman correlation test were performed to determine the differences in knowledge and use of the vegetation among villages, as well as in the gender and age group of the respondents. Nevertheless, we found no significant differences (P>0.05). The use value (UV) was calculated to analyze the use of flora. in order to assess the relationship between the UV and their ecological importance, the index of adjusted ecological importance value (AEIV) was obtained. We detected that the most used species are not necessarily those of greater ecological importance. The potentially useful flora was defined based on a literature research, in situinterviews, as well as on their visual and morphological characteristics. According to the data, more than 50% of the inventoried species are potentially useful, mainly as ornamental and medicinal ones, and they provide new economic alternatives for the local people with a minimum impact on the rainforest.